2004
DOI: 10.1002/esp.1108
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of vegetation barriers for marly sediment trapping

Abstract: Vegetation barriers can be effective in trapping eroded sediment, but little knowledge exists on the characteristics of vegetation barriers efficient in trapping all sediments from an eroded zone upslope. The objective of this study is to quantify the effectiveness of vegetation barriers for marly sediment trapping. Relationships between eroded zones and vegetation barriers -composed of low vegetation, that is to say herbaceous and under-shrub layers -located downslope and sufficient to stop all the sediments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 21 publications
3
39
0
5
Order By: Relevance
“…These heterogeneous patterns are very important in controlling water runoff and soil loss (Rey, 2004), and some research (Valentin et al, 1999;Martínez Raya et al, 2006) documented the banded or stripped pattern of vegetation would reduce much more water runoff and increase productivity. Thus we should pay attention on the vegetation pattern design for vegetation restoration (Ma et al, 2004b;Li et al, 2006c).…”
Section: Discussionmentioning
confidence: 99%
“…These heterogeneous patterns are very important in controlling water runoff and soil loss (Rey, 2004), and some research (Valentin et al, 1999;Martínez Raya et al, 2006) documented the banded or stripped pattern of vegetation would reduce much more water runoff and increase productivity. Thus we should pay attention on the vegetation pattern design for vegetation restoration (Ma et al, 2004b;Li et al, 2006c).…”
Section: Discussionmentioning
confidence: 99%
“…With a longer flow path to the sinks, there is a higher probability that sediment will be trapped by impedances (Kirkby, 2001;Kirkby et al, 2002;Blanco-Canqui et al, 2004;Rey, 2004) and, therefore, the SEAs close to sinks contribute more sediment. As illustrated by the distribution of SW (Fig.…”
Section: Catchment Connectivitymentioning
confidence: 99%
“…There is runoff generation and sediment export from vegetation patches, although it is rather low compared to that of bare soil. In addition, the position of source areas is an important factor in the hydrological process (Rey, 2004;Bracken and Croke, 2007). Serious soil erosion will occur in the source areas with a larger runoff supply area in the upper slope.…”
Section: Cover Pattern Measurementmentioning
confidence: 99%
“…Moved soil particles also have more opportunity to deposit or be trapped by vegetation barriers (Wilcox et al, 2003;Cammeraat, 2004). It was reported that vegetation with a given area positioned near the bottom of a slope is more effective in retaining sediment and runoff at the plot and hillslope scale (Rey, 2004;Li et al, 2008;Ding et al, 2010). These lead to the limited utility of these indices.…”
Section: Efficiency Of Indicesmentioning
confidence: 99%